Cleanlines, Health, Safety and Enviromental Sustainable (CHSE) Implementation on Cau Chocolates Tourism Object - Negara, Ni Luh Gede Aris Maytadewi; Dharmayanti, Cokorda Istri; Aryani, Ni Made Citra (GLOBAL HEALTH SCIENCE GROUP, 2024)
The tourism industry is one of the sectors most affected during the Covid-19 pandemic. Covid-19 certainly has an impact on all sectors in the tourism sector and of course has an impact on tourist villages as tourist destinations.Tourists experience concerns about security when visiting and staying in tourist villages and tourist village managers also experience concerns about the possibility of spreading the virus. The implementation of CHSE in tourist attractions is very important to create a safe, comfortable and memorable tourist experience for visitors, as well as contributing to environmental sustainability and growth of the tourism industry. Analysis of the implementation of CHSE at the CAU Cokelat tourist attraction is deemed necessary to ensure the health and safety of visitors and workers. This research is quantitative study with cross sectional design. Analysis of the fulfillment of the CHSE guidelines at the CAU chocolates tourism object was carried out, using the CHSE guidelines instrument released by the Ministry of Tourism and Creative Economy. This activity has been carried out on August 9, 2024. The results showed that CAU chocolates tourism object was able to meet 91% of the CHSE guidelines. Descriptively, the conclusion from this research is that CAU Chocolates Tourism Object has been able to implement 91% of the CHSE guidelines, which is a good result for ensuring the health and safety of visitors.